Pengaruh Ukuran Perusahaan, Kebijakan Hutang, Profitabilitas, Likuiditas Terhadap Kebijakan Dividen pada Perusahaan Wholesale/Retail di Bursa Efek Indonesia - Angeline Setiawan; Liyi Sumira Purba; Annisa Nauli Sinaga; Sherly Estenia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to examine and analyze how the influence of Company Size, Debt Policy, Profitability, Liquidity Against Dividend Policy in Wholesale / Retail Companies Listed on the Indonesia Stock Exchange Period 2015-2019. The research method uses quantitative and descriptive approaches. The population in this study is the overall number of Wholesale / Retail sector companies listed on the Indonesia Stock Exchange, amounting to 63 companies. The sample of this study were 11 companies with a purposive sampling method. The data analysis technique is multiple linear regression analysis. Partially shows that profitability has a positive and significant effect on dividend policy on Wholesale / Retail companies listed on the Indonesia Stock Exchange in the 2015-2019 period. While Company Size, Debt Policy, Liquidity have no effect and are not significant on dividend policy at Wholesale / Retail companies listed on the Indonesia Stock Exchange for the period of 2015-2019. And simultaneously Company Size, Debt Policy, Profitability, Liquidity have significant and significant effect on dividend policy on Wholesale / Retail companies listed on the Indonesia Stock Exchange for the period of 2015-2019. The magnitude of the coefficient of determination is 29.2% while the remaining 70.8% dividend policy is explained by other variables not examined in this study. The conclusion of this study is that partially only profitability has a positive and significant effect on dividend policy on Wholesale / Retail companies listed on the Indonesia Stock Exchange in the period 2015-2019. Keywords: Company Size, Debt Policy, Profitability, Liquidity, and Dividend Policy